Dual Control of Host Actin Polymerization by a Legionella Effector Pair - M. Pillon; C. Michard; N. Baïlo; J. Bougnon; K. Picq; O. Dubois; C. Andrea; L. Attaiech; V. Daubin; S. Jarraud; E. Kay; P. Doublet (Cellular Microbiology)
Host actin cytoskeleton is often targeted by pathogenic bacteria through the secretion of effectors. Legionella pneumophila virulence relies on the injection of the largest known arsenal of bacterial proteins, over 300 Dot/Icm type 4 secretion system effectors, into the host cytosol. Here, we define the functional interactions between VipA and LegK2, two effectors with antagonistic activities towards actin polymerization that have been proposed to interfere with the endosomal pathway. We confirmed the prominent role of LegK2 effector in Legionella infection, as the deletion of legK2 results in defects in the inhibition of actin polymerization at the Legionella-containing vacuole, as well as in endosomal escape of bacteria and subsequent intracellular replication. More importantly, we observed the restoration of the ΔlegK2 mutant defects, upon deletion of vipA gene, making LegK2/VipA a novel example of effector-effector suppression pair that targets the actin cytoskeleton and whose functional interaction impacts L. pneumophila virulence. We demonstrated that LegK2 and VipA do not modulate each other’s activity in a “metaeffector” relationship. Instead, the antagonistic activities of the LegK2/VipA effector pair would target different substrates, Arp2/3 for LegK2 and G-actin for VipA, to temporally control actin polymerization at the LCV and interfere with phagosome maturation and endosome recycling, thus contributing to the intracellular life cycle of the bacterium. Strikingly, the functional interaction between LegK2 and VipA is consolidated by an evolutionary history that has refined the best effector repertoire for the benefit of L. pneumophila virulence.